Project Spraoi: two year outcomes of a whole school physical activity and nutrition intervention using the RE-AIM framework. Issue 2 (3rd April 2019) - O'Leary, Mai; Rush, Elaine; Lacey, Seán; Burns, Con; Coppinger, Tara
Abstract : We aimed to assess the impact of Project Spraoi: a school-based physical activity (PA) and nutrition intervention that reached 473 primary school children and 43 school staff in Cork (Ireland). Four primary schools (2 intervention, 2 control) with similar characteristics participated and for 2 school years, intervention schools were assigned an 'Energizer', who promoted PA and healthy eating. A subsample of children from the intervention schools ( n = 106) and matching controls ( n = 125) had measures of body mass, waist circumference, blood pressure, fitness, nutritional knowledge/attitudes and PA recorded at baseline and after 2 school years. Process evaluation techniques assessed the impact of the intervention on teachers, parents and children. Analysis of covariance revealed the intervention was associated with smaller waist circumference relative to gender and age ( p < 0.0005), slower resting heart rate ( p = 0.003) and favourable nutritional attitudes among 10 year olds. No significant change across other variables or among 6 year olds was found. Teachers, parents and children reported positive outcomes for PA behaviour and nutritional knowledge/attitudes. Project Spraoi has shown to improve heart rate and prevent further gains in fat mass amongst older aged children. The positive impact of the intervention supports the need for its continued delivery, particularly as children age.